The state of oxidative processes in testicular tissue samples after ionizing radiation - M. A. Al Meselmani (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Aim. To study of oxidative processes in testicular tissues after gamma irradiation. Material and methods. Using the polarographic method, the rate of oxygen absorption on endogenous and exogenous substrates (Vend, Vsuc, Vglu, Vdnf) and with specific inhibitors of tissue respiration of amytal and sodium malonate (Vam, Vmal) in testicular tissues at different times (3, 10, 40 days) after total single gamma irradiation (1.0 Gr). Results. It was found that, in the testicular tissues of rats at different times (3rd, 10th, 40th day) after total single gamma irradiation (1.0 Gy). In the early period (72 hours) after irradiation, (Vend) decreased by 14.7 % (p < 0.05), (Vsuc) by 18.6 % (p < 0.05) and (Vglu) by 10.9 % (p < 0.05) compared with the control. After 10 days, on the contrary, there was an increase in (Vend) by 108.2 % (p < 0.05), in the presence of exogenous succinate and glutamate substrates, increased (Vsuc) by 45.1 % (p < 0.05) and (Vglu) by 112 % (p < 0.05), SDdnf decreased by 12.8 % (p < 0.05), and with inhibitors, low-resistance respiration (MRD) increased by 9.4 % (p < 0.05). On day 40 (Vend, Vsuc, Vglu) increased by 120.7 % (p < 0.05), 124.8 % (p < 0.05) and 97.1 % (p < 0.05), respectively, SDdnf decreased by 11.5 % (p < 0.001), amytal resistant respiration (ARD) by 30.6 % (p < 0.05) and MRD by 11.7 % (p < 0.05). Conclusion. Increased oxygen uptake was accompanied by a significant decrease in SDdnf in both experimental groups (10th and 40th days), which suggested the threat of disconnection of oxidation and phosphorylation processes. A decrease in MPD also indicates a decrease in the contribution of fatty acids (FA) to the energy supply of testicular tissue.